"Oceans without Borders": Dialectics of Transcolonial Labor Migration from the Indian Ocean World to the Atlantic Ocean World1. (21st July 2015) - Hurgobin, Yoshina; Basu, Subho
Abstract: By investigating the hitherto unstudied trans-colonial migration between Mauritius and the Caribbean in the nineteenth century, this article complicates liberal Eurocentric perceptions of global labor force formation under the auspices of colonial capital. Indeed, coercion, as depicted in liberal historiography, was a crucial component of indentured migration but indentured workers themselves sometimes availed of the opportunity of the global demand for their labor by engaging in trans-colonial migration. The dialectic of the formation of globalized indentured labor regime was such that while capital sought to confine workers to specific plantations, the very nature of the demand for labor enabled workers to defy the dictates of capital and further enabled them to move from one colony to another in search of better livelihoods and thus made them globally mobile. These migrations did not follow the so-called boundaries between the Indian Ocean and the Atlantic Ocean. Rather such migrations reflected workers' search for jobs through trans-colonial networks within the framework of imperial domination.